Testicular Ischemia Due to a Band Around the Spermatic Cord - Artul, Suheil (J Clin Imaging Sci, 2015)
We present a case of an 18-year-old boy who was admitted to our hospital with a 2-day history of pain in the right scrotum. Ultrasound examination showed signs of ischemia, with dampened testicular arterial flow and bell-clapper deformity. Surgery revealed a constricting fibrous band around the distal spermatic cord resembling the bell-clapper deformity.